Sleep Apnea Syndrome: Prevalence and Comorbidity with Other Non-communicable Diseases and HIV Infection, among Hospitalized Patients in Yaoundé, Cameroon. (10th February 2022) - Massongo, Massongo; Ngarka, Leonard; Balkissou, Dodo Adamou; Poka-Mayap, Virginie; Sonwa, Steve Voufouo; Tatah, Godwin Y.; Nfor, Leonard N.; Mengnjo, Michel K.; Chokoke, Eric-Samuel; Moutlen, Ben Patrick Michel; Perrig, Stephen; Pefura-Yone, Eric Walter; et al.
Abstract : Background . Sleep apnea syndrome (SAS), a growing public health threat, is an emerging condition in sub-Saharan Africa (SSA). Related SSA studies have so far used an incomplete definition. This study is aimed at assessing SAS using an American Academy of Sleep Medicine (AASM) complete definition and at exploring its relationship with comorbidities, among patients hospitalized in a Cameroonian tertiary hospital. Methods . This cross-sectional study was conducted in cardiology, endocrinology, and neurology departments of the Yaoundé Central Hospital. Patients aged 21 and above were consecutively invited, and some of them were randomly selected to undergo a full night record using a portable sleep monitoring device, to diagnose sleep-disordered breathing (SDB). SAS was defined as an apnea − hypopnea index AHI ≥ 5 /h, associated with either excessive daytime sleepiness or at least 3 compatible symptoms. Moderate to severe SAS (MS-SAS) stood for an AHI ≥ 15 / h . We used chi-square or Fisher tests to compare SAS and non-SAS groups. Findings . One hundred and eleven patients presented a valid sleep monitoring report. Their mean age ± standard deviation (range) was 58 ± 12.5 (28–87) years, and 53.2% were female. The prevalence (95% confident interval (CI)) of SAS was 55.0 (45.7, 64.2)% and the one of MS-SAS 34.2 (25.4, 43.1)%. The obstructive pattern (90.2% of SAS and 86.8% of MS-SAS) was predominant. The prevalence of SAS among specific comorbidities ranged from 52.2% to 75.0%. Compared to SAS free patients, more SAS patients presented with hypertension (75.4% vs. 48.0%, p = 0.005 % ), history of stroke (36.7% vs. 32.0%, p = 0.756 ), cardiac failure (23.0% vs. 12.0%, p = 0.213 ), and combined cardiovascular comorbidity (80.3% vs. 52.0%, p = 0.003 ). Similar results were observed for MS-SAS. Metabolic and neuropsychiatric comorbidities did not differ between SAS and SAS-free patients. Conclusion . The SAS diagnosed using modified AASM definition showed high prevalence among patients hospitalized for acute medical conditions, as it was found with SDB. Unlike HIV infection, metabolic and brain conditions, cardiovascular comorbidities (hypertension and cardiac failure) were significantly more prevalent in SAS patients.